Collaborative treatment of erectile dysfunction: thoughts from the membership of the Sexual Medicine Society of North America - Hagey, Derek Willis (Kansas State University, 2012)
Recent years have seen a rise in the medicalization of treatments for erectile dysfunction (ED). While there has been a divide between the medical and psychological communities, some have called for a more collaborative relationship. Little research has been done on the collaboration between medical professionals and psychotherapists in treating ED. This study seeks to increase current knowledge about medical professionals’ referral practices and communication post-referral. An online survey was developed and distributed to the members of the Sexual Medicine Society of North America (SMSNA) (N = 541). Survey questions inquired as to the factors that increased participants’ willingness to refer ED patients, the form of communication participants currently desire to have with psychotherapists and the participants’ desired level of communication with psychotherapists to whom they might refer. Less than ten percent of the medical professionals invited to participate in the study completed the survey (n=50). Those who did complete the survey were primarily male, specialized in urology and practiced in the U.S. Almost half the respondents were employed in an academic setting while just over half of respondents worked in hospital-based, group, or solo practices. Just over half of the survey participants practiced in urban areas. Although the number of medical professionals who completed the survey was small, findings indicated that those who completed a sexual medicine fellowship and who had a larger percentage of their patient population being seen for ED were more likely to refer patients to psychotherapists. Participants who have referred ED patients to psychotherapists reported little-to-no communication between them and the psychotherapists to whom they refer. The study participants expressed a desire to refer patients to psychotherapists who are experienced in working with both sexual and couples issues. Questions about the desires and experiences of medical professionals who have not referred to psychotherapists were not able to be answered because of the limited number of these individuals in the data set. Although the number of participants who completed the survey limits the generalizability of the data, this study demonstrates that most medical professionals who responded to the survey are willing to refer ED patients to psychotherapists.
Keywords: Medical Family Therapy; Marriage and Family Therapy; Individual & Family Studies (0628)